2009
DOI: 10.2503/jjshs1.78.356
|View full text |Cite
|
Sign up to set email alerts
|

Cell Division and Expansion Growth during Rose Petal Development

Abstract: There have been few reports on the morphology of flower opening, despite its horticultural significance. It is not clear when cell division stops during rose petal development or what changes occur in cell morphology. This study aims to clarify the details of cell morphological changes during rose petal development. Rose (Rosa hybrida L. 'Sonia') petals were sampled in six flower bud stages. Cell morphological changes were observed by light microscopy, transmission and scanning electron microscopy using cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…In G. grandiflora (Koning, 1984) and T. caerulea (Norikoshi et al, 2013), only two phases have been observed: cell division and expansion, and cell expansion. In rose petals, similar findings have been reported, although cell division continues in the final stage of flower opening (Yamada et al, 2009b). It is unclear whether the presence of the four phases is specific to Eustoma.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…In G. grandiflora (Koning, 1984) and T. caerulea (Norikoshi et al, 2013), only two phases have been observed: cell division and expansion, and cell expansion. In rose petals, similar findings have been reported, although cell division continues in the final stage of flower opening (Yamada et al, 2009b). It is unclear whether the presence of the four phases is specific to Eustoma.…”
Section: Discussionsupporting
confidence: 69%
“…This finding suggests that stored starch is degraded to soluble carbohydrates because large amounts of soluble carbohydrates are required for flower opening in Eustoma (Shimizu and Ichimura, 2005). The disappearance of plastids has also been observed in rose petals (Yamada et al, 2009b). Similarly, a decrease in starch content in petals has been reported in rose (Evans and Reid, 1988;Ho and Nichols, 1977) and gladiolus (Yamane et al, 1991).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations